Impact of pyrochar and hydrochar derived from digestate on the co-digestion of sewage sludge and swine manure. (October 2020) - Xu, Suyun; Wang, Chongyang; Duan, Yuting; Wong, Jonathan Woon-Chung
Highlights: Impacts of hydrochar and pyrochar on anaerobic digestion were compared. Both hydrochar and pyrochar present positive effects. The maximum methane yield of 308.4 mL/g VS was found in HTC digester. Methane yield of HTC was 27% and 49% higher than HC and the control reactor. Superiority of hydrochar is related to its more abundant surface functional groups. Abstract: Four kinds of biochar were obtained by pyrolysis carbonization and hydrothermal carbonization from swine manure digestate, i.e. pyrochar (HC, HC-Fe) and hydrochar (HTC, HTC-Fe). Batch fermentation was conducted to compare their effects on the co-digestion of sewage sludge and swine manure. Both pyrochar and hydrochar present positive effect on methane production, nevertheless the higher methane yields were obtained in HTC and HTC-Fe digesters. No advantage was observed for the iron impregnation. The maximum methane yield was 308.4 mL/g VS in HTC digester, which was 27% and 49% higher than HC and Control, respectively. The surface functional groups of hydrochar are more abundant than pyrochar, which is favorable for promoting the syntrophic anaerobic metabolism, as revealed by the promoted substrate hydrolysis and VFAs consumption rate. Thus, it is proposed to convert swine manure digestate to hydrochar, which can be recirculated back to the AD reactor to increase the digestion efficiency.